2019
DOI: 10.3390/app9020302
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption and Financial Development in NAFTA Countries, 1971–2015

Abstract: To satisfy human needs and desires, it is necessary to produce goods and services that require the use of some production factors, such as labor, capital, and energy, among others. Nowadays, energy is a key production factor for economic activity in all countries. The main objective of this paper is to analyze the relationship between energy, economic growth, urbanization, and financial development in the country-members of the North American Free Trade Agreement (NAFTA) during the period of 1971-2015. Panel d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…The study concluded a negative and statistically significant effect from financial development to energy consumption. In addition, numerous studies conducted by Ali, Yusop, and Hook (2015), by Farhani and Solarin (2017), by Kahouli (2017), by Gómez and Rodríguez (2018) found a negative link between financial development and energy consumption. Table 1, summarizes the findings on the financial development-energy consumption nexus in the case of different countries.…”
Section: Literature Reviewmentioning
confidence: 96%
“…The study concluded a negative and statistically significant effect from financial development to energy consumption. In addition, numerous studies conducted by Ali, Yusop, and Hook (2015), by Farhani and Solarin (2017), by Kahouli (2017), by Gómez and Rodríguez (2018) found a negative link between financial development and energy consumption. Table 1, summarizes the findings on the financial development-energy consumption nexus in the case of different countries.…”
Section: Literature Reviewmentioning
confidence: 96%
“…In a recent study, Ref. [51] used the data from the North American Free Trade Agreement (NAFTA) Member countries and performed several tests including cross-section dependence. However, they found a negative relationship between energy consumption and financial development.…”
Section: Empirical Evidence From Preceding Studiesmentioning
confidence: 99%
“…Energy is one of the key elements in producing most goods and services and is essential for promoting economic growth [1][2][3]. However, the rapid increase in energy consumption has placed tremendous pressure on the environment.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Through full-sample analysis by dividing the sample into three sub-samples (eastern, central, and western China), the authors further analyzed the regional differences and found that the inhibitory effect of financial development on energy consumption was largest in the western region, followed by the eastern region and then the central region. Gomez and Rodriguez [3] researched the influence of financial development on energy consumption in North American Free Trade Agreement (NAFTA) countries using a series of panel data methods and panel data from 1971 to 2015 and found a negative relationship between financial development and energy consumption.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%